IMPACT OF VITAMIN D SUPPLEMENTATION ON GLYCEMIC CONTROL IN TYPE 2 DIABETIC PATIENTS (The Research of Medical Science Review, 2025)
OBJECTIVES: To evaluate the impact of vitamin D supplementation on glycemic control in type 2 diabetic patients when added to standard anti-diabetic therapy.METHODOLOGY: A case-control study was conducted at the Combined Military Hospital, Sialkot, over six months. A total of 170 participants with type 2 diabetes were enrolled using non-probability consecutive sampling. Group A (n=85) received 5000 IU/day of oral vitamin D for three months alongside anti-diabetic medications, while Group B (n=85) continued standard therapy alone. Baseline and post-intervention levels of HbA1C and serum vitamin D were assessed. Data were analyzed using SPSS v20, with a p-value ≤ 0.05 considered statistically significant.RESULTS: Baseline characteristics were comparable between groups (p > 0.05). After three months, Group A demonstrated a significant reduction in mean HbA1C (from 7.18 ± 1.03% to 6.71 ± 0.89%, p = 0.002) and an increase in serum vitamin D levels (from 36.5 ± 8.7 to 64.2 ± 10.3 nmol/L, p < 0.001). No significant changes were observed in the control group. Stratified analysis confirmed consistent results across age, gender, and BMI.CONCLUSION: Vitamin D supplementation significantly improves glycemic control in type 2 diabetes patients and may serve as a beneficial adjunct to conventional therapy. Further large-scale studies are warranted to establish it in clinical guidelines.